Fluid restriction in term neonates with moderate to severe perinatal asphyxia: A randomised controlled trial - Dr.Vasudha Tomar; Dr. Ruchi Rai; Dr. D. K. Singh (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Management of newborns who suffer perinatal asphyxia is primarily based on supportive management, of which fluid and electrolyte management plays a very important role. We studied the role of restriction of fluids in the first 72 h in term neonates suffering from moderate to severe perinatal asphyxia.Methods: Term newborns with moderate to severe perinatal asphyxia were randomised to receive full or restricted fluids (25 newborns each) during the first 72 h of life. The primary outcome measures were mortality and neurological status at discharge.Results: Mortality among the full (FF) and restricted fluid (RF) groups was not significantly different, 4 in the FF group and 3 in the RF group with a relative risk (RR) of 1.52 [confidence interval (CI) 0.38-6.04]. The neurological status at discharge was also comparable in both the groups with RR (CI) 0.61 (0.22-1.7).Conclusion: Routine restriction of fluids in term neonates with moderate to severe perinatal asphyxia does not have any advantage.